Effects of Fermented Tempeh Using Rhizopus oligosporus and Lactobacillus rhamnosus GG on Body Weight, Lee Index, High Sensitivity C Reactive Protein and Lipid Profile of Obese Rats - Fatih Az Zahra; Faizah Fulyani; Nani Maharani; Gemala Anjani; Etika Ratna Noer (Journal of Biomedicine and Translational Research, 2023)
Background: Tempeh is a fermented soybean containing isoflavones that shows good benefits again obesity. Co-fermentation of tempeh using  Lactobacillus rhamnosus GG could increase the bioavailability of isoflavones.Objective: This study aimed to determine the effect of co-fermented tempeh using Lactobacillus rhamnosus GG (tLGG) on body weight (B.W.), Lee Index, high sensitivity C Reactive Protein (hs-CRP), and lipid profile of obese rats. Total flavonoid and genistein were also measured.Methods: Male Sprague Dawley rats (n=36, 200-to-215-gram, age eight weeks) were orally administered high fat and high sucrose diet (HFHS diet) for two weeks to induce obesity. After obesity was confirmed by checking Lee Index, rats were divided into six group and administered orally standard diet (normal control), HFHS diet (negative control), HFHS diet and 120 mg/kg B.W./day-orlistat (positive control), HFHS diet and 60 mg/kg B.W./day standard tempeh  with Rhizopus oligosporus (tS), HFHS diet and 60 mg/kg B.W./day tLGG, HFHS diet and 120 mg/kg B.W./day tLGG for four weeks. Body weight, Lee Index, hs-CRP, and lipid profile were analyzed. Total flavonoid and genistein were analyzed.Results: 120 mg/kg B.W./day tLGG group exhibited significantly lower body weight gains, Lee Index, hs-CRP, triglyceride, total cholesterol, LDL, and higher HDL compared to negative control and tS group (p<0,001), however, positive control group exhibited lower body weight gains compared to tLGG group (p<0,001). Nevertheless, tLGG group exhibited lower Lee Index compared to positive control group.   tLGG showed higher flavonoid and genistein level than tS.Conclusion: Administration of 120 mg/kg B.W./day tLGG showed significantly lower Lee Index compared to all groups given HFHS diet, however, positive control group showed lower body weight gains compared to tLGG group. tLGG also improved hs-CRP and lipid profile two times better than negative control group. tLGG increased total flavonoids and genistein level.